Norcantharidin induce apoptosis in human nasopharyngeal carcinoma through caspase and mitochondrial pathway. Issue 3 (29th November 2017) - Chen, Andy Wei‐Ge; Tseng, Yen‐Shuo; Lin, Chia‐Chieh; Hsi, Yi‐Ting; Lo, Yu‐Sheng; Chuang, Yi‐Ching; Lin, Shu‐Hui; Yu, Chia‐Yun; Hsieh, Ming‐Ju; Chen, Mu‐Kuan
Abstract: While Nasopharyngeal carcinoma (NPC) is uncommon in western countries, it is endemic in Southeast Asia and Southern China. Previous study of norcantharidin (NCTD), isolated from blister beetles, has proved its anticancer effect on various tumors. However, the effect of NCTD in NPC has never been studied. The purpose of this study is to inspect the suppression activity of NCTD on NPC, along with the underlying mechanism. NPC cell line NPC‐BM was treated with NCTD. NCTD remarkably inhibited proliferation and induce apoptosis in NPC‐BM cell. Activation of caspase‐3, −8, −9 was observed through western blotting. The expression of antiapoptotic protein Bcl‐XL was significantly reduced, but expression of proapoptotic protein Bak was increased after treatment of NCTD. The cytotoxic effect of NCTD on NPC‐BM cell is mainly due to apoptosis, mediated by caspase and mitochondrial pathway. These results suggested that NCTD could be a potential anticancer agent for NPC.